1991
DOI: 10.1126/science.1654594
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory Synaptic Responses Mediated by GABA A Receptors in the Hippocampus

Abstract: Gamma-aminobutyric acid (GABA) is a major inhibitory neurotransmitter in the cortex. Activation of postsynaptic GABAA receptors hyperpolarizes cells and inhibits neuronal activity. Synaptic responses mediated by GABAA receptors also strongly excited hippocampal neurons. This excitatory response was recorded in morphologically identified interneurons in the presence of 4-aminopyridine or after elevation of extracellular potassium concentrations. The synaptic excitation sustained by GABAA receptors synchronized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
128
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(142 citation statements)
references
References 21 publications
13
128
1
Order By: Relevance
“…Shortly after, Voskuyl and Albus (1985) identified 2 types of spontaneous, interictal-like field potentials in isolated hippocampal slices; the first type resembled the spontaneous epileptiform activity induced by GABA A receptor antagonists and originated in the CA3 subfield, while the second lasted longer, spread at slower velocity and was resistant to glutamatergic receptor antagonism. These results were later confirmed by other investigators (Rutecki et al, 1987;Michelson and Wong, 1991;Perreault and Avoli, 1992;Watts and Jefferys, 1993).…”
Section: Gaba Receptor Antagonistssupporting
confidence: 81%
See 1 more Smart Citation
“…Shortly after, Voskuyl and Albus (1985) identified 2 types of spontaneous, interictal-like field potentials in isolated hippocampal slices; the first type resembled the spontaneous epileptiform activity induced by GABA A receptor antagonists and originated in the CA3 subfield, while the second lasted longer, spread at slower velocity and was resistant to glutamatergic receptor antagonism. These results were later confirmed by other investigators (Rutecki et al, 1987;Michelson and Wong, 1991;Perreault and Avoli, 1992;Watts and Jefferys, 1993).…”
Section: Gaba Receptor Antagonistssupporting
confidence: 81%
“…The "slow" glutamatergic-independent spikes recorded in the CA3 subfield during 4AP application are associated with transient increases in extracellular [K + ] that are caused by the activation of GABA A receptors following the release of GABA from interneurons (Morris et al, 1996). In line with this view, Benardo (1997) has found in rat neocortical slices that interneurons generate periodic action potential firing in the presence of 4AP and excitatory transmission blockers while large amplitude IPSPs occur rhythmically in pyramidal cells; he also suggested that under these pharmacological conditions, interneurons are synchronized through electrotonic coupling and recurrent collaterals (which release GABA thus causing postsynaptic GABA A receptor depolarizations as proposed in the hippocampus by Michelson and Wong, 1991).…”
Section: K + Channel Blockersmentioning
confidence: 70%
“…The resultant increase in extracellular glutamate content was not as dramatic as that previously observed in the striatum, and this change by itself cannot account for the convulsive activity, because it was observed only with the three highest 4-AP concentrations used, whereas the epileptiform discharges occurred also with lower concentrations. The remarkable enhancement of extracellular GABA induced by 4-AP might also be involved in the hyperexcitation, because it has been repeatedly shown in hippocampal slices that under conditions of neuronal overactivity (Staley et al, 1995;Kaila et al, 1997;Labrakakis et al, 1997), including that induced by 4-AP (Michelson and Wong, 1991;Perrault and Avoli, 1992;Lamsa and Kaila, 1997;Siniscalchi et al, 1997), the synaptic action of this neurotransmitter changes from inhibitory to excitatory. Nonetheless, as with glutamate, GABA content increases were observed only with the highest 4-AP concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Interneuron communication is provided by glutamatergic transmission (Lacaille, 1991) but also by GABA A receptor postsynaptic currents that are frankly excitatory (Michelson and Wong, 1991) along with gap junctions containing specific types of connexin proteins (Gibson et al, 1999(Gibson et al, , 2004Traub et al, 2003Traub et al, , 2004Mancilla et al, 2007).…”
Section: Interneurons As Gaba Releasing Nerve Cellsmentioning
confidence: 99%